Key Trends in Implementing the Fund's Transparency Policy. (Policy Papers; Policy Paper, 2022)
This report provides an overview of recent developments in the implementation of the Fund's Transparency Policy, as required by the Executive Board. It covers documents considered by the Board in 2020 and their respective publication status up to June 2021. To provide some perspective on trends, it compares the implementation of the Fund's Transparency Policy on the 2020 documents with preceding years.